SHORT AND LONG-TERM PRICE ELASTICITY OF ROOM DEMAND-A TOOL FOR REVENUE MANAGEMENT: A HOTEL CASE STUDY IN BALI - Ida Bagus Made Wiyasha; I Nyoman Arcana (Journal of Management and Business, 2015)
Room revenue is one of the biggest revenues in the hotel industry which is cited in the literature contributed 70-75% to total hotel revenue. Due to these roles, extant studies have been done in room revenue management. This study applied archival data to answer the proposed research questions. Prior to conducting empirical research personal approaches have been done by contacting directly hotel managers in resort area of Nusa Dua Bali to see the possibility of obtaining theneeded data. We got information that data on revenues especially rooms were prohibited for research activities. It may only be used for internal hotel use only. The managerial implications of this study are the following. First, that the management of MBLH hotel should design itsroom rate structures in such a way that could capture the dynamics of the seasons and guest segments. Second, that the management of MBLH hotel should review its policy on marketing especially on room rates contracts with all of its partners. The findings of this study areapplicable only for the MBLH hotel and thus they cannot be generalized for hotels in Bali. Second, the length of daily observation covered only for 488 daily observations. It needs a longer daily observation to achieve a better result. Based on those limitations it is strongly suggested to conduct a similar study covering all classes of hotels all over Bali province with longer daily observations.